The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1093/g3journal/jkac238
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of mutational patterns induced by formaldehyde and acetaldehyde reveal similarity to a common mutational signature

Abstract: Formaldehyde (CH2O) and acetaldehyde (C2H4O) are reactive small molecules produced endogenously in cells as well as being environmental contaminants. Both of these small aldehydes are classified as human carcinogens, since they are known to damage DNA and exposure is linked to cancer incidence. However, the mutagenic properties of formaldehyde and acetaldehyde remain incompletely understood, at least in part because they are relatively weak mutagens. Here, we use a highly sensitive yeast genetic reporter syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Depending on the mutagen, the ssDNA reporter can be two to three orders of magnitude more sensitive than dsDNA controls [35]. Indeed, this system has been deployed successfully to elucidate the characteristics of multiple mutagens already [35,[50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the mutagen, the ssDNA reporter can be two to three orders of magnitude more sensitive than dsDNA controls [35]. Indeed, this system has been deployed successfully to elucidate the characteristics of multiple mutagens already [35,[50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…The cdc13-1 ssDNA triple reporter gene system has been used previously to elucidate the mutagenic properties of: sodium bisulfite and the human APOBEC3G cytidine deaminase [35]; abasic sites [50]; reactive oxygen species [51]; human APOBEC3A and APOBEC3B cytidine deaminases [52]; alkylating agents [53]; acetaldehyde [54,55]; and formaldehyde [55].…”
Section: Increased Glucose Metabolism Leads To Increased Mutagenesismentioning
confidence: 99%
“…(Figure ). In fact, most cancers are marked by replication stress, replication–transcription collisions and R-loop formation, and hypertranscription, all events that generate copious ssDNA. , As such, mutations in ssDNA regions could represent a genomic record of aldehyde exposures, such as what we and others have demonstrated. , …”
Section: Mutagenicity Of Aldehydesmentioning
confidence: 99%
“…Interestingly, the enriched mutations observed in cancers strongly associated with the nontranscribed strand of genes, which suggests that ssDNA formed during increased transcription in cancers likely acts as an ideal substrate for acetaldehyde-induced mutagenesis . A related study demonstrated the mutagenesis of ssDNA in response to acetaldehyde, albeit with different base substitutions, i.e., more C → T and T → A changes; interestingly, acetaldehyde treatment led to an increase in the proportion of ssDNA-associated deletions of ≥5 bp but without any associated microhomology at break points …”
Section: Mutagenicity Of Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation